Monitoring Virulence Phenotypes of Bremia lactucae in South and Southeast Brazil - da Silva Carvalho, Lívia Tálita [UNESP]; Vargas, Pablo Forlan [UNESP]; Okuma, Izabella Garbeline [UNESP]; Marin, Marcus Vinícius; de Mello Prado, Renato [UNESP]; da Silva Neto, Jorge Moreira [UNESP]; Jacinto, Ana Carolina Pires; Castoldi, Renata (Wiley, 2025)
Lettuce downy mildew (Bremia lactucae) is one of the most important diseases of lettuce, especially in conditions of mild temperatures and high humidity. The great variability of B. lactucae makes the use of genetic control complex, as resistance to different virulence phenotypes requires different resistance factors. Dm (“Downy mildew”) genes or resistance factors, have been widely used in lettuce cultivars, providing a high level of resistance to downy mildew. The objective of this work was to monitor and study the virulence phenotypes of B. lactucae in the south and southeast regions of Brazil. Samples with downy mildew symptoms were collected in the main producing areas of the states of São Paulo, Rio de Janeiro, Rio Grande do Sul, Santa Catarina and Paraná. Subsequently, a race differentiation test was carried out by inoculating differentiating cultivars and observing the pathogen's response, and a sextet code was assigned to each isolate according to its virulence phenotype (EU-C). Frequency (%), virulence complexity index by isolate and by phenotype, and Gleason index were calculated. A total of 117 isolates were evaluated and 61 virulence phenotypes were identified. The sextet code 31-00-00 was the most frequent and could be used for the evaluation of resistant cultivars in the states of the south and southeast regions of Brazil. The resistance factor of lettuce cultivar Balesta provided resistance to all evaluated isolates, while RYZ2164 was resistant to all isolates except those from Paraná. Additionally, Kibrille conferred resistance to isolates from Santa Catarina.
Keywords: downy mildew; Lactuca sativa; resistance; virulence phenotype